Organic Fertilizer Titonia Plus and Micro Nutrients Improved Rice (Oryza sativa L.) Production in Koto Panjang and Koto Tingga, Padang City, West Sumatera, Indonesia - Rozen, Nalwida; Gusnidar, Gusnidar; Hakim, Nurhajati (Journal of Tropical Crop Science, 2020)
A series of on-farm fi eld experiments were conducted in two locations in Padang, Koto Panjang and Koto Tingga, West Sumatera, Indonesia in 2015. The purpose of the experiment was to establish the formula of organic fertilizer derived from Tithonia supplied with micro nutrients, Zn and Mn, on rice. The experiments were conducted using completely-randomized block design with six treatments and three replications. The treatments were P = Tithonia Organic Fertilizer Plus (TOFP) + 3.0 kg Mn.ha-1, Q = TOFP + 3.0 kg Mn.ha-1+ 3.0 kg Zn.ha-1, R = TOFP + 4.5 kg Mn.ha-1 + 6 kg Zn.ha-1, S= TOFP + 4.5 kg Mn.ha-1+ 9 kg Zn.ha-1, T = TOFP only, U = 100% chemical fertilizer only. Treatment with micro nutrients as addition to TOFP (TOFP+ 3.0 kg Mn.ha-1 and TOFP+ 3.0 kg Mn.ha-1+3.0 kg Zn.ha-1) increased rice grain yield by 80 g per clump.